Does Ceruloplasmin Defend Against Neurodegenerative Diseases? - Wang, Bo; Wang, Xiao-Ping (Current Neuropharmacology, 2019)
Ceruloplasmin (CP) is the major copper transport protein in plasma, mainly produced by the liver. Glycosylphosphatidylinositol-linked CP (GPI-CP) is the predominant form expressed in astrocytes of the brain. A growing body of evidence has demonstrated that CP is an essential protein in the body with multiple functions such as regulating the homeostasis of copper and iron ions, ferroxidase activity, oxidizing organic amines, and preventing the formation of free radicals. In addition, as an acute-phase protein, CP is induced during inflammation and infection. The fact that patients with genetic disorder aceruloplasminemia do not suffer from tissue copper deficiency, but rather from disruptions in iron metabolism shows essential roles of CP in iron metabolism rather than copper. Furthermore, abnormal metabolism of metal ions and oxidative stress are found in other neurodegenerative diseases, such as Wilson’s disease, Alzheimer’s disease and Parkinson’s disease. Brain iron accumulation and decreased activity of CP have been shown to be associated with neurodegeneration. We hypothesize that CP may play a protective role in neurodegenerative diseases. However, whether iron accumulation is a cause or a result of neurodegeneration remains unclear. Further research on molecular mechanisms is required before a consensus can be reached regarding a neuroprotective role for CP in neurodegeneration. This review article summarizes the main physiological functions of CP and the current knowledge of its role in neurodegenerative diseases.
Keywords: neurodegenerative diseases